The role of lean manufacturing (Toyota model) in entrepreneurship for organisations/an analytical study of the opinions of a sample of workers at the Arab Integration Factory in Al-Muthanna Governorate - Assistant Lect. Osamah Hawee Azeez Al-Tai (Zien Journals, 2024)
The current research sought to identify the role of lean manufacturing in entrepreneurship for medium and small-sized organizations, clarify the intellectual relationship between the two variables, and test the relationship of correlation and effect between them in the field. The problem of the research was to find solutions for medium and small-sized organizations to face competitive challenges, and to obtain a market position so that they can survive and grow in a very complex, dynamic environment, by answering the main question of the research, which is what is the relationship of correlation and effect between the variable of lean manufacturing as an independent variable and the variable entrepreneurship as a dependent variable? The practical aspect of the research was applied in the Arab Integration Factory for the production and packaging of tomato paste. The researcher adopted the descriptive analysis approach in answering the research questions, as the sample was randomly selected from the individuals working in the factory, and the questionnaire was distributed electronically to (159) working individuals. The answer was given by only (150) respondents, and these are the questionnaires that were used for statistical analysis. The researcher used descriptive statistics, Pearson correlation, and (SEM).The research reached a set of conclusions, the most important of which is the existence of a statistically significant correlation and effect between lean manufacturing and entrepreneurship for organizations. In light of the conclusions, the researcher presented a set of recommendations, the most important of which was that the factory management should adopt the concept of lean manufacturing in all its dimensions and apply it in a clear and understandable way. For all working individuals, efforts towards achieving this are supported by the senior management
Keywords: Lean Manufacturing; Entrepreneurship; Toyota Manufacturing System